2015
DOI: 10.1002/chir.22526
|View full text |Cite
|
Sign up to set email alerts
|

Superficially Porous Particle Based Hydroxypropyl‐β‐cyclodextrin Stationary Phase for High‐Efficiency Enantiomeric Separations

Abstract: A superficially porous particle (SPP)-based hydroxypropyl-β-cyclodextrin (HPBCD) chiral stationary phase (CSP) was produced and its chromatographic performance was compared to both 5 µm and 3 µm fully porous particle (FPP)-based CSPs. The relative surface coverage of the HPBCD chiral selector on each particle was approximately equal, which resulted in equivalent enantiomeric selectivity (α) values on each phase when constant mobile phase conditions were used. Under such conditions, the SPP column resulted in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Even today's state of the art high performance instruments can potentially limit the "true" performance of a chromatography column. In our experience as well as that of others [3,5,[10][11][12][13], even current generation instrumentation can contribute as much as 30-60% to peak variance for short, narrow bore columns. Remedial focus is often on injection ports and connections tubing as these are easily changed.…”
Section: Introductionsupporting
confidence: 72%
“…Even today's state of the art high performance instruments can potentially limit the "true" performance of a chromatography column. In our experience as well as that of others [3,5,[10][11][12][13], even current generation instrumentation can contribute as much as 30-60% to peak variance for short, narrow bore columns. Remedial focus is often on injection ports and connections tubing as these are easily changed.…”
Section: Introductionsupporting
confidence: 72%
“…Armstrong and co‐workers undoubtedly offered a wide comprehensive work in evaluation of SPPs for chiral separations. They bonded hydroxypropyl‐β‐cyclodextrin, cyclofructan‐6 based selectors, teicoplanin, its aglycone, and vancomycin on 2.7 μm SPPs . Focusing on the kinetic behavior, they showed the chiral SPPs outperform their FPPs counterparts in all working conditions ranging from normal phase to polar organic mode to HILIC.…”
Section: Enantioselective Uhplc By Direct Approachmentioning
confidence: 99%
“…Hydroxypropyl-β-cyclodextrin, cyclofructan-6 based selectors, teicoplanin, and vancomycin were also recently bonded on 2.7 μm SPPs. [210][211][212][213] It was found that chiral SPPs Chiral separations are still one of the workhorses for SFC since the analysis and production of enantiomerically pure compounds is still a major topic of interest when active pharmaceutical ingredients are concerned. There are a lot of improvements that were brought to chiral SFC analysis thanks to the use of modern systems and columns packed with small particles.…”
Section: Automated Tools For Methods Development In Chromatographymentioning
confidence: 99%